About the literary tales of B. Suleimenov (Eurasian Journal of Philology Science and Education, 2023)
The article discusses the trends in the development of modern children's literature on the basis of literary fairy tales. Taking the literary fairy tales of the modern Kazakh children's writer B. Suleimenov as the subject of the study, the function of the fairy tale genre in the children’s upbringing is scientifically analyzed. The writer wrote for children the fairy tales like “Zhanaikai”, “Gorilla Adam”, “Tugan kuninmen, Aitumsyk!”, “Zhyrtkysh balyk zhaily khikaya”, “Alabai-Dalabay”, “Africany arkalagan Kaka”, “Kyrannyn kanaty zhylaidy”, consisting of two stories “Khan Shatyrdan – Kun shatyrga sayakhat!”. By grouping, systematyzing, analyzing the writer's fairy tales, it was established that the vast majority of his works were about animals. While analyzing the literary fairy tales, the issue of continuity of centuries-old traditions and innovation in children's literature received an attention. Content searches in the writer's fairy tales are evaluated within the framework of traditions and innovations in national literature. In the differentiation of literary and aesthetic achievement in modern children's prose, the writer's fairy tales on animals were analyzed.The author, based on the opinion of domestic and foreign scientists on the fairy tales genre, came to a conclusion about the similarity and difference between traditional fairy tales and author's fairy tales. The searches of the modern children's writer B. Suleimenov in choosing a theme serve to complement the content of literary fairy tales. From the fairy tales about animals, the cognitive function of a literary work was revealed, and the contribution to the upbringing of future generation was emphasized by the author's position.Key words: children's literature, prose, fiction, fairy tale, fantasy fairy tale, household fairy tale, author's fairy tale.